Management and Outcomes of Button Batteries in the Aerodigestive Tract: A Multi‐institutional Study. (18th February 2020) - Shaffer, Amber D.; Jacobs, Ian N.; Derkay, Craig S.; Goldstein, Nira A.; Giordano, Terri; Ho, Sandra; Kim, Bong J.; Park, Albert H.; Simons, Jeffrey P.
Abstract : Objectives/Hypothesis: To describe the clinical presentation, management, and complications associated with button battery impaction in the aerodigestive tract in children. Study Design: Retrospective case series. Methods: This multi‐institutional study, endorsed by the American Society of Pediatric Otolaryngology research consortium, is a retrospective medical record review, including all children at five tertiary‐care institutions presenting with button batteries impacted in the aerodigestive tract between January 2002 and December 2014. Battery type/size, duration and location of impaction, presenting symptoms, treatment, complications, and outcomes were examined. Results: Eighty‐one patients were included (64.2% male), with ingestion witnessed in 20 (24.7%). Median age at presentation was 3 years (range, 1 week–14 years). Median time from diagnosis to removal was 2.5 hours (range, 0.4–72 hours). Locations included the esophagus (n = 48), hypopharynx (n = 1), stomach (n = 6), nasal cavity (n = 22), and ear canal (n = 4). Most common symptoms for esophageal/hypopharyngeal impactions included dysphagia (26.5%), nausea/vomiting (26.5%), drooling (24.5%), cough (18.4%), and fever (18.4%). Most common symptoms for nasal impactions included epistaxis (54.6%), rhinorrhea (40.9%), nasal pain (27.3%), and fever (22.7%). Almost all esophageal impactions were from 3‐V (89.5%), 20‐mm (81.8%) lithium batteries. Severe esophageal complications included stricture (28.6%), perforation (24.5%), tracheoesophageal fistula formation (8.2%), pneumothorax (4.1%), and bilateral true vocal fold paresis (4.1%). Nasal complications included necrosis (59.1%), septal perforation (27.3%), and saddle nose deformity (4.5%). Duration of impaction correlated with an increased likelihood of persistent symptoms only for nasal batteries ( P = .049). Conclusions: Button batteries in the upper pediatric aerodigestive tract or ear canal should be considered a surgical emergency, requiring urgent removal and careful vigilance for complications. Level of Evidence: 4 Laryngoscope, 131:E298–E306, 2021